Cross-platform analysis reveals cellular and molecular landscape of glioblastoma invasion. Issue 3 (28th July 2022) - Chen, Ann T; Xiao, Yang; Tang, Xiangjun; Baqri, Mehdi; Gao, Xingchun; Reschke, Melanie; Sheu, Wendy C; Long, Gretchen; Zhou, Yu; Deng, Gang; Zhang, Shenqi; Deng, Yanxiang; et al.
Abstract: Background: Improved treatment of glioblastoma (GBM) needs to address tumor invasion, a hallmark of the disease that remains poorly understood. In this study, we profiled GBM invasion through integrative analysis of histological and single-cell RNA sequencing (scRNA-seq) data from 10 patients. Methods: Human histology samples, patient-derived xenograft mouse histology samples, and scRNA-seq data were collected from 10 GBM patients. Tumor invasion was characterized and quantified at the phenotypic level using hematoxylin and eosin and Ki-67 histology stains. Crystallin alpha B (CRYAB) and CD44 were identified as regulators of tumor invasion from scRNA-seq transcriptomic data and validated in vitro, in vivo, and in a mouse GBM resection model. Results: At the cellular level, we found that invasive GBM are less dense and proliferative than their non-invasive counterparts. At the molecular level, we identified unique transcriptomic features that significantly contribute to GBM invasion. Specifically, we found that CRYAB significantly contributes to postoperative recurrence and is highly co-expressed with CD44 in invasive GBM samples. Conclusions: Collectively, our analysis identifies differentially expressed features between invasive and nodular GBM, and describes a novel relationship between CRYAB and CD44 that contributes to tumor invasiveness, establishing a cellular and molecular landscape of GBM invasion.